Tìm số tự nhiên x , biết

Question

Tìm số tự nhiên x , biết

tim-so-tu-nhien-biet

in progress 0
Delwyn 8 tháng 2020-10-17T15:44:33+00:00 1 Answers 76 views 0

Answers ( )

  1. Giải thích các bước giải:

    $11/$ $240 : (x – 5) = 2^{2} . 5^{2} – 20$

               $240 : (x – 5) = 4 . 25 – 20$

               $240 : (x – 5) = 100 – 20$

               $240 : (x – 5) = 80$

               $x – 5 = 240 : 80$

               $x – 5 = 3$

               $x = 3 + 5$

               $x = 8$

            $Vậy$ $x = 8$

    $12/$ $70 : (x – 3) = (3^{4} – 1) : 4 – 10$

               $70 : (x – 3) = (81 – 1) : 4 – 10$

               $70 : (x – 3) = 80 : 4 – 10$

               $70 : (x – 3) = 20 – 10$

               $70 : (x – 3) = 10$

               $x – 3 = 70 : 10$

               $x – 3 = 7$

               $x = 7 + 3$

               $x = 10$

         $Vậy$ $x = 10$

    $13/$ $75 : (x + 2) = 5^{3} – (3^{2} + 4^{2}) . 2^{2}$

               $75 : (x + 2) = 125 – (9 + 16) . 4$

               $75 : (x + 2) = 125 – 25 . 4$

               $75 : (x + 2) = 125 – 100$

               $75 : (x + 2) = 25$

               $x + 2 = 75 : 25$

               $x + 2 = 3$

               $x = 3 – 2$

               $x = 1$

           $Vậy$ $x = 1$

    $14/$ $260 : (x + 4) = 5 (2^{3} + 5) – 3 (3^{2} + 2^{2})$

               $260 : (x + 4) = 5 (8 + 5) – 3 (9 + 4)$

               $260 : (x + 4) = 5 . 13 – 3 . 13$

               $260 : (x + 4) = (5 – 3) . 13$

               $260 : (x + 4) = 2 . 13$

               $260 : (x + 4) = 26$

               $x + 4 = 260 : 26$

               $x + 4 = 10$

               $x = 10 – 4$

               $x = 6$

          $Vậy$ $x = 6$

    $15/$ $(2^{2} + 3)(x – 5) + 14 = 5^{2} + 124 : 2^{2}$

               $(4 + 3)(x – 5) + 14 = 25 + 124 : 4$

               $7 (x – 5) + 14 = 25 + 31$

               $7 (x – 5) + 14 = 56$

               $7 (x – 5) = 56 – 14$

               $7 (x – 5) = 42$

               $x – 5 = 42 : 7$

               $x – 5 = 6$

               $x = 6 + 5$

               $x = 11$

            $Vậy$ $x = 11$

    $16/$ $3^{2} (x + 1) – 3 = 2^{3} + (7^{2} . 2) : 14$

               $9 (x + 1) – 3 = 8 + (49 . 2) : 14$

               $9 (x + 1) – 3 = 8 + 98 : 14$

               $9 (x + 1) – 3 = 8 + 7$

               $9 (x + 1) – 3 = 15$

               $9 (x + 1) = 15 + 3$

               $9 (x + 1) = 18$

               $x + 1 = 18 : 9$

               $x + 1 = 2$

               $x = 2 – 1$

               $x = 1$

            $Vậy$ $x = 1$

    $17/$ $2^{2} . 3 (x + 5) – 6^{2} = (2^{3} + 2^{2}) . 2^{2}$

               $4 . 3 (x + 5) – 36 = (8 + 4) . 4$

               $4 . 3 (x + 5) – 36 = 12 . 4$

               $4 . 3 (x + 5) – 36 = 48$

               $4 . 3 (x + 5) = 48 + 36$

               $4 . 3 (x + 5) = 84$

               $3 (x + 5) = 84 : 4$ 

               $3 (x + 5) = 21$

               $x + 5 = 21 : 3$

               $x + 5 = 7$

               $x = 7 – 5$

               $x = 2$

           $Vậy$ $x = 2$

    $18/$ $(2^{2} + 1)(x + 14) = 5^{2} . 4 + (2^{5} + 3^{2} + 7^{2}) : 2$

               $(4 + 1)(x + 14) = 25 . 4 + (32 + 9 + 49) : 2$

               $5 (x + 14) = 100 + (41 + 49) : 2$

               $5 (x + 14) = 100 + 90 : 2$

               $5 (x + 14) = 100 + 45$

               $5 (x + 14) = 145$

               $x + 14 = 145 : 5$

               $x + 14 = 29$

               $x = 29 – 14$

               $x = 15$

          $Vậy$ $x = 15$

    $19/$ $(2^{2} – 1)(x – 1) = 2^{2} + (6^{2} + 2^{6}) : (5^{2} . 2)$

               $(4 – 1)(x – 1) = 4 + (36 + 64) : (25 . 2)$

               $3 (x – 1) = 4 + 100 : 50$

               $3 (x – 1) = 4 + 2$

               $3 (x – 1) = 6$

               $x – 1 = 6 : 2$

               $x – 1 = 3$

               $x = 3 + 1$

               $x = 4$

          $Vậy$ $x = 4$

    $20/$ $(3^{2} – 2)(x – 12) + 35 = 5^{2} + 279 : 3^{2}$

               $(9 – 2)(x – 12) + 35 = 25 + 279 : 9$

               $7 (x – 12) + 35 = 25 + 31$

               $7 (x – 12) + 35 = 56$

               $7 (x – 12) = 56 – 35$

               $7 (x – 12) = 21$

               $x – 12 = 21 : 7$

               $x – 12 = 3$

               $x = 3 + 12$

               $x = 15$

          $Vậy$ $x = 15$

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )